2004
DOI: 10.14507/epaa.v12n21.2004
|View full text |Cite
|
Sign up to set email alerts
|

Income and financial aid effects on persistence and degree attainment in public colleges

Abstract: This study examined the distribution of financial aid among financially dependent four-year college students and the effectiveness of different types of financial aid in promoting student persistence and timely bachelor’s degree attainment. The findings of descriptive statistical and logistic regression analyses using the NCES Beginning Postsecondary Students (1990-94) data show that subsidized loans taken in the first year of college have a positive effect on persistence. The first-year distribution of aid do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 49 publications
1
34
0
2
Order By: Relevance
“…See Alon (2005) and Dowd (2004) for a fuller discussion of how these statistical biases may affect estimates of the effects of financial aid on student outcomes. 3.…”
Section: Resultsmentioning
confidence: 99%
“…See Alon (2005) and Dowd (2004) for a fuller discussion of how these statistical biases may affect estimates of the effects of financial aid on student outcomes. 3.…”
Section: Resultsmentioning
confidence: 99%
“…Findings from these studies provide mixed evidence regarding the effects of loans (i.e. positive, negative, no effect) on student persistence and degree attainment (see Dowd 2004Dowd , 2008Pascarella and Terenzini 2005). These mixed results could be attributed to differences in the samples selected, statistical techniques employed, time period under investigation, and primary outcome variable of interest (Dowd 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Loans even have negative effect on African-American students (Perna, 2000). Although another study found no significant difference in the effect of loans by income quartile in a sample of full-time students in the public four-year sector (Dowd, 2004), the author speculated that the failure to find differential effects may be due to the small sample of students in the upper income quartiles.…”
Section: Financial Aidmentioning
confidence: 92%